Jingle all the way - Macomber, Debbie (New York : Ballantine Books, 2020)
A young workaholic avoiding home for the holidays discovers that you can't run away from who you are.
A novel.
Keywords: Mothers and daughters -- Fiction; Blizzards -- Fiction; Voyages and travels -- Fiction; Vacations -- Fiction; Illinois -- Fiction; Romance fiction; Christmas fiction